Palmistry - Gardini, Maria (London Ebury Press, 1988)
An illustrated guide to palmistry, explaining the terms and techniques used in palm classification and analysis, and showing how the interpretations derived from palm reading can provide an insight into personality and the whole range of human relationships.
Include Color Illustration, Bibliography and Index
Keywords: Palmistry